Integrated Metabolomics and Network Pharmacology Study on the Mechanism of Kangfuxiaoyan Suppository for Treating Chronic Pelvic Inflammatory Disease - Zhang, Zhengyi; Xie, Ziye; Lv, Shujing; Shi, Yulian; Zhai, Chuanjia; Li, Xuejiao; Qiao, Bin; Gao, Xiaoyan (Frontiers in Pharmacology, 2022)
Kangfuxiaoyan suppository (KFXYS) is a commonly used traditional Chinese medicine (TCM) preparation for the treatment of chronic pelvic inflammatory disease (CPID) clinically, and its safety and effectiveness have been well verified. However, the potential mechanism remains unclear. The integrated strategy of metabolomics and network pharmacology was employed in the study to reveal the potential mechanism of KFXYS in the treatment of CPID. Our research consists of 5 steps. First, the effect of KFXYS in reversing uterine inflammation indexes was verified. Second, based on the comprehensive characterization of 123 chemical ingredients of KFXYS, the ingredients of KFXYS absorbed into blood were identified by UPLC-Q-TOF/MS, then ADME research was carried out on the main ingredients. Third, the differential metabolites with significant correlation to inflammatory indexes were discovered by metabolomics and correlation analysis. Fourth, the potential targets and pathways of KFXYS in treating CPID were predicted by network pharmacology based on the ingredients which had good ADME behavior. Fifth, the proteins in common pathways of metabolomics and network pharmacology were used to screen the key targets from the potential targets of network pharmacology, and the potential mechanism of KFXYS in treating CPID was clarified. As a result, KFXYS significantly reversed the uterine inflammation indexes, including IL-1 and IL-6. The ingredients absorbed into blood including matrine, sophocarpine, aloin, esculetin-O-glucuronide, 7,4'-dihydroxyisoflavone-O-glucuronide, and 4'-methoxyisoflavone-7-O-glucuronide had good ADME behavior in vivo. Among the differential metabolites, Leukotriene A4, 5-Hydroxyindoleacetic acid, Ornithine, Arginine, and PC (20:1(11Z)/20:4(8Z,11Z,14Z,17Z)) were significant correlation to inflammation indexes. The integration analysis of metabolomics and network pharmacology shows that KFXYS may regulate the key targets including ARG1, NOS2, NOS3, etc. We speculate that ingredients of KFXYS, such as matrine, sophocarpine, aloin etc. act on the key proteins including ARG1, NOS2, and NOS3, to exert anti-inflammatory effect.